IMPLEMENTATION OF PRACTICE-ORIENTED APPROACH IN THE TRAINING OF FUTURE BACHELORS IN AGRICULTURAL ENGINEERING - Kovalchuk, Vasyl; Lychova, Tetiana; Reva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Modern trends in the labour market of Ukrainian agricultural sector place high demands on the professional expertise and training of future Agricultural Engineers. Agricultural sector of Ukraine is currently experiencing an acute shortage of human resources capable of adapting rapidly to new social and economic conditions, mobile and competitive in the world labour market. In this case, the development of professional competence is an important requirement risen for future Agricultural Engineering bachelors’ training. The article discusses the essence of the practice-oriented approach used for future Agricultural Engineering bachelors’ training and identifies effective practice-oriented technologies for their training future. The experiment was conducted at Hlukhiv Agrotechnical institute named after S. A. Kovpak, Sumy National Agrarian university. 90 undergraduate students, 15 university teachers participated in the study and 18 representatives of employers. The study was aimed at identifying effective training technologies targeted at developing Agricultural Engineers’ skills necessary in the labour market. In order to conduct experiment a questionnaire was developed to identify teaching and learning problems as well as students’ requests to improve the educational process. The survey also identified the most effective training technologies and those that didn’t find their widespread practical use.Practice-oriented technologies facilitate future Agricultural Engineering bachelors’ professional activities during their training in higher education institutions. These include contextual learning technologies, design technologies, case-study technologies, interactive technologies, problem-based technologies, portfolio-based technologies, master class technologies.